From Prevention to Care: The Crucial Role of Physicians, Nursing, Laboratory Services, Health Administration, and Emergency Medical Services in Infection Control - Faten Mohammed Islam Khotany; Feryal Mohammed Islam; Amirah Hamed Jaber Alharthi; Abdulaziz M Islam Khotani; Shuruq Iqal Al Nadwi; Ghadeer H. Alhazmi; Duaa M. Mandeeli; Amal H. Almuwalled; Fawziah Adam Hawsawi; Mahacen Egal Al Nadwi; Fardus Mohammed Islam Khawtani; Laila Hussien Hakami (International Journal of Medical Toxicology and Legal Medicine, 2024)
Introduction: Infection prevention and control is an important component of healthcare delivery that seeks to prevent and contain spread of infectious diseases in healthcare facilities. Infection control interventions involvecollaboration of physicians, nurses, laboratory, health administrative and the emergency medical services. All the professions provide different skills and knowledge required in the early detection, control and handling of infections within health care settings. Aim of work: To provide a comprehensive understanding of the crucial role of physicians, nursing, laboratory services, health administration, and emergency medical services in infection control Methods: We conducted a comprehensive search in the MEDLINE database's electronic literature using the following search terms: Role, Physicians, Nursing, Laboratory Services, Health Administration, Emergency Medical Services and Infection Control. The search was restricted to publications from 2016to 2024 in order to locate relevant content. We performed a search on Google Scholar to locate and examine academic papers that pertain to my subject matter. The selection of articles was impacted by certain criteria for inclusion. Results: The publications analyzed in this study encompassed from 2016 to 2024. The study was structured into various sections with specific headings in the discussion section. Conclusion:Engaging physicians, nurses, laboratory services, health administrators as well as EMS providers, optimizes infection control in the healthcare system. These professionals are joined together in interdisciplinary infection control committees where they get to discuss new trends, problems and ways of dealing with them. Such an environment leads to the integration of infectious prevention, in which clinical, administrative, and laboratory knowledge is aligned with frontline practicality, flexibility, and adaptability. Both professions contribute to healthcare systems in their own ways and knowledge, practices from both, help to reduce infection hazards significantly. In this way, these healthcare professionals guarantee an effective infection control system, and therefore healthy patient populations – overall, the public.